Femtosecond spin-state photo-switching dynamics in an FeIII spin crossover solid accompanied by coherent structural vibrations1. Issue 30 (14th August 2015) - Bertoni, R.; Lorenc, M.; Laisney, J.; Tissot, A.; Moréac, A.; Matar, S. F.; Boillot, M.-L.; Collet, E.
<x xml:space="preserve">Abstract</x> Femtosecond optical spectroscopy reveals coherent structural trapping accompanying spin-state photoswitching in a FeIII spin-crossover material.